The formation of opportunity beliefs: overcoming ignorance and reducing doubt - Shepherd, Dean A.; McMullen, Jeffery S.; Jennings, P. Devereaux (Strategic Entrepreneurship Journal, 2007)
Abstract Although (opportunity) beliefs are becoming increasingly recognized as fundamental to understanding entrepreneurial cognition and strategic action, little is understood about the mechanisms that are responsible for the formation and evolution of these beliefs. Introducing the mechanisms of gists, matching, and updating from philosophy's and psychology's coherence theory, we propose a theoretical framework to explain how third‐person opportunity beliefs (beliefs that one has recognized an opportunity for someone with the right knowledge and motivation) are formed and how they evolve to become first‐person opportunity beliefs (beliefs that one has recognized an opportunity for himself or herself). We conclude by examining how the model contributes to literatures ranging from entrepreneurial cognition and action, to strategic myopia and organizational attention, to opportunity recognition, discovery, and creation. Copyright © 2007 Strategic Management Society.